The Practice of Religious Moderation Based on Theo-anthropocentric in Indonesian Islamic Boarding Schools: A Phenomenological Study - Umiarso; Muhammad Qorib (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Religious moderation was an important value in the life of modern society. The article aimed to anayze the practice and implications of religious moderation in Indonesian Islamic boarding schools based on theo-anthropocentric values. This research was qualitative field research with a phenomenological approach. The source of the research data was Islamic boarding schools in Indonesia and taken by representatives of the regions of East Java and Southeast Sulawesi as one of the largest Islamic boarding schools in Indonesia. The research participants were 30 people including, the leaders of the pesantren, the caretakers of the pesantren, and the students of two major Islamic boarding schools in East Java. Data collection was done by interview technique. The data analyst follows a procedure that begins with data collection, data reduction, data presentation, and conclusion drawing. This result showed three main keys to the practice of religious moderation. First, the practice of moderation was in harmony between technology or theory and its application in the field. Second, the moderation attitude in the pesantren and its environment could prevent the emergence of radicalism. Third, this moderation practice also fosters and forms a tolerant and democratic attitude toward all the differences that exist. The results of this study could serve as a simple guide in applying of diversity moderation in other areas. The existence of limitations on the validity of the data and the depth of analysis was a note that needs to be completed in the future. Keywords: Religious Moderation, Theoanthropocentric, Theoanthropocentric Islamic Education